Effect of benfluralin on Pinus pinea seedlings mycorrhized with Pisolithus tinctorius and Suillus bellinii – Study of plant antioxidant response - Franco, A. R. (2016)
In this study, Pinus pinea seedlings mycorrhized with selected ectomycorrhizal fungi (ECMF), Pisolithus tinctorius and Suillus bellinii, were exposed to the herbicide benfluralin. Non-mycorrhized P. pinea seedlings and seedlings mycorrhized with ECMF were transferred to benfluralin-spiked soils at levels of 0.165, 1.65 and 16.5 mg kg 1. Plant growth and the fungal role on plant antioxidant response were assessed. In the presence of benfluralin, higher plant growth was observed in mycorrhized plants compared to non-mycorrhized plants, but ECMF colonisation and nutrient uptake were affected by the herbicide. Benfluralin showed no effect on lipid peroxidation in P. pinea seedlings. However, seedlings mycorrhized with S. bellinii showed higher levels of lipid peroxidation when compared to non-mycorrhized ones, both in the presence and absence of benfluralin. The increase of lipid peroxidation could be related to seedling growth induced by the fungus and not to benfluralin toxicity. A similar trend was observed in seedlings mycorrhized with P. tinctorius when exposed to higher benfluralin concentrations, suggesting that the antioxidant response to benfluralin is related not only to fungus species, but also to the level of stress applied in the soil. The higher amount of superoxide dismutase activity in P. pinea seedlings tissues exposed to benfluralin could indicate a plant adaptative response to benfluralin toxicity. Catalase activity showed no increase with benfluralin exposure. Pre-established P. tinctorius mycorrhization conferred root protection and enhanced plant growth in benfluralin spiked soil, inferring that P. tinctorius – P. pinea association could advantageous for plant growth in soils contaminated with pesticides